Drug-induced thrombocytopenia – etiology and alternative therapeutic approaches - Rajashekaraiah, Vani; Berikai Ananthakrishna, Anusha (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. The cumulative incidence of drug-induced thrombocytopenia (DIT) is 10 cases per one million people per year with a prevalence of approximately 25% in critically ill patients. This review provides a comprehensive view of drug-induced thrombocytopenia, diagnosis, underlying mechanisms, common strategies in therapeutics, and potential alternatives. Material and methods. Databases such as “Google Scholar”, “PubMed”, “Medline” and “MDPI” was used for literature review with the keywords, “platelets”, “platelet disorders”, “thrombocytopenia”, “drug-induced”, “oxidative stress” “plant extracts”, “phytochemicals”, “antioxidants”, for the articles published between 2013-2023 and written in the English language. Analysis of the literature. Several antimicrobials, anti-cancer drugs, and antivirals are often reported to cause adverse effects during treatment, such as thrombocytopenia. A thorough understanding of the underlying pathophysiology is important for appropriate treatment. Even though an improvement in platelet count is observed after the discontinuation of the causative drug, there is a dire need for treatment in some cases due to associated complications. There are various pitfalls with conventional treatments which include clinical complications and lack of effectiveness. Conclusion. Interventions in therapeutics through antioxidants can aid in faster recovery. Various plant extracts and phytochemicals have been employed as therapeutics in platelet disorders due to their exceptional antioxidant activity. It is imperative to explore the bioactive components of natural products and their influence on platelet efficacy. Also, it highlights how antioxidants can be used as a safe, yet effective option as therapeutics for treating a complicated disorder such as DIT or be used as supplements to prevent adverse effects of existing treatments involving antibiotics and chemotherapeutics.
Keywords: alternative therapeutics; drug-induced thrombocytopenia; phytochemicals; platelets